1989
DOI: 10.1002/anr.1780320311
|View full text |Cite
|
Sign up to set email alerts
|

Binding of double‐stranded DNA to glomeruli of rats in vivo

Abstract: In vivo binding of double‐stranded DNA (dsDNA) to renal glomeruli of rats was examined. 125I‐dsDNA (600 basepairs) was perfused with 131I‐IgG as a blood marker into the right renal artery of normal rats, and blood flow was restored. After 10 minutes, isolated glomeruli showed a specific uptake of DNA, which increased in a saturable fashion with increasing doses of administered DNA. To exclude the possibility that 125I in the glomeruli represented only DNA breakdown products, we extracted the DNA from the glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…23,24 These studies have focused exclusively on large (>1000 base pairs), random dsDNA sequences, despite collagen's demonstrated avidity for short (<200 base pairs) DNA regardless of strandedness. 7,10 We found that short (<100 nucleotides), monodisperse ssDNA oligomers complex with type I collagen to form selfassembled fibers. Upon mixing dilute solutions of ssDNA and collagen, not only fibrils (<1 μm), but large self-assembled fibers (>10 μm) formed rapidly (<120 min) and spontaneously (Figure 1).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…23,24 These studies have focused exclusively on large (>1000 base pairs), random dsDNA sequences, despite collagen's demonstrated avidity for short (<200 base pairs) DNA regardless of strandedness. 7,10 We found that short (<100 nucleotides), monodisperse ssDNA oligomers complex with type I collagen to form selfassembled fibers. Upon mixing dilute solutions of ssDNA and collagen, not only fibrils (<1 μm), but large self-assembled fibers (>10 μm) formed rapidly (<120 min) and spontaneously (Figure 1).…”
mentioning
confidence: 99%
“…One such interaction is the complexation of DNA and collagen, first discovered in 1976 while investigating the accumulation of DNA and anti-DNA antibody complexes in the tissue of patients with autoimmune diseases such as rheumatoid arthritis and systemic lupus erythematosus. ,,,,− From these investigations, it was identified that both single-stranded DNA (ssDNA) and double-stranded DNA (dsDNA) readily bind to the collagenous component of the glomerular basement membrane. Specifically, DNA binds to type I, II, and IV collagens and not to fibronectin or the reference protein, bovine serum albumin. In fact, complexes of DNA and anti-DNA antibodies require DNA first to bind to the basement membrane and then to interact with the anti-DNA antibody to accumulate at the basement membrane rather than as preformed DNA–anti-DNA complexes in solution. , Important to these findings was the effect of DNA structure on DNA–collagen complexation. DNA length mediated the process, favoring shorter DNA while being independent of DNA strandedness. , These investigations, though, were conducted using enzyme-linked immunosorbent assays. − ,, Missing from these studies was demonstration of collagen’s ability to undergo fibrillogenesis–collagen triple helix self-assembly into fibrils. No observation of fibrillogenesis or the structure of this interaction was made at the time.…”
mentioning
confidence: 99%
See 3 more Smart Citations